Psychometric properties of the Mexican version of the Intolerance of Uncertainty Scale: The IUS-12M - Hernández-Posadas, Alejandrina (2023)
Background: The Intolerance of Uncertainty Scale short version (IUS-12) has proven to be a robust self-report measure to assess intolerance of uncertainty. While previous psychometric analyses of the IUS-12 have established a stable two-factor structure corresponding to the prospective and inhibitory factors of intolerance of uncertainty, recent studies suggest that the bifactor model may better explain its factor structure. Objective: The current study aimed to adapt and validate the IUS-12 in a Mexican population culturally. Method: The study consisted of a convenience non-probabilistic community sample of 405 adults between 18 and 70 years. Results: Confirmatory factor analyses supported a bifactor model and good internal consistency. Invariance testing indicated partial invariance across women and men. Convergent validity tests showed that the IUS-12 was related to measures of worry, as well as depression and anxiety. Conclusion: These findings provide evidence for the reliability and validity of the adapted version of the IUS-12 in Mexico.